Social Dominance Orientation and Trust in Institutions among Macedonian and Albanian Young Adults - Frichand, Ana; Blazhevska Stoilkovska, Biljana (Филозофски факултет, Скопје, 2016)
This study analyzes the relationship between social dominance orientation and trust in institutions among young adults of Macedonian and Albanian ethnicity. Total number of 133 respondents (78 Macedonians and 55 Albanians), from 20 until 30 years of age, with different levels of education (finished high school, students/graduated and higher), participated in the research. Macedonians are all declared as Orthodox Christians, while Albanians are all declared as Muslims. All participants are from Skopje and currently live in the capital. Findings are mostly in line with the results from other similar studies. It could be plausible that Macedonian young adults are more oriented towards social dominance, since they belong to the majority group. However, those who trust more the education system are less socially dominant. On the other side, regarding social dominance orientation, Albanians are less socially dominant and this is probably because they represent the minority group. In terms of trust in institutions, Albanian young adults are more prone to trust religious institutions, as well as media, EU and health care system. As for Macedonians, they have more trust in the Macedonian Army, although such difference is not very strong. Findings are further discussed and elaborated in terms of their importance and applicability.
Keywords: social dominance orientation, trust in institutions, Macedonians, Albanians, young adults